IOP-lowering effect of glaucoma surgery: retrospective analysis - I.B. Alekseev; M.M. Soshina; K.I. Bel'skaja; А.К. Aylarova; Yu.G. Kopchenova; I.A. Koroleva; A.R. Isaev (РМЖ "Клиническая офтальмология")
I.B. Alekseev1, M.M. Soshina2, K.I. Bel'skaja1, A.K. Ajlarova1,2, Yu.G. Kopchenova3, I.A. Koroleva4, A.R. Isaev1 1Russian Medical Academy of Continuous Professional Education, Moscow, Russian  Federation 2Moscow City Ophthalmological Center of S.P. Botkin City Clinical Hospital, Moscow, Russian Federation 3City Clinical Hospital No. 52, Moscow, Russian Federation 4City Clinical Hospital No. 15, Moscow, Russian Federation Aim: to assess IOP-lowering effect of the first glaucoma surgery depending on disease stage, age, and sex as well as IOP-lowering medication regimen before re-surgery. Patients and Methods: retrospective analysis of inpatient and outpatient medical records of 93 patients who underwent glaucoma re-surgery was performed. Results: mean interval between two glaucoma surgeries was 83 months (89.2 months in men and 76.6 months in women). The duration of IOP-lowering effect of the first glaucoma surgery (depending on disease stage) was 84 months at stage 1, 93.6 months at stage 2, 80.4 months at stage 3, and 62.7 months at stage 4. Tonography was performed in 32 of 93 patients (34.4%). Outflow facility coefficient (C) was 0.03 to 0.18 mm3/min/mm Hg (on average, 0.08 mm3/min/mm Hg). Minute volume of the aqueous (F) was 0.1 to 1.6 mm3/min (on average, 0.56 mm3/min). Becker’s coefficient was 89 to 933 (on average, 287.9). Conclusions: female sex, older and senile age, and advanced disease stage reduce the duration of IOP-lowering effect of glaucoma surgery. Critical flicker fusion rate is more informative tool to assess optic nerve in case of optical opacities. Informative value of tonography in postoperative patients is less than in naive patients. Nevertheless, tonography provides valuable data on intraocular hydrodynamics and the effects of IOP-lowering drugs (in particular, when prescribed or changed). It was demonstrated that prostaglandin analogues are the major group of topical IOP-lowering medications (86%). The more advanced disease stage was, the more groups of topical IOP-lowering medications were prescribed before re-surgery. Keywords: glaucoma, glaucoma surgery, intraocular pressure, IOP-lowering effect, tonography, prostaglandin analogues, β-blockers. For citation: Alekseev I.B., Soshina M.M., Bel'skaja K.I. et al. IOP-lowering effect of glaucoma surgery: retrospective analysis. Russian Journal of Clinical Ophthalmology. 2020;20(1):–14. DOI: 10.32364/2311-7729-2020-20-1-8-14.